1989
DOI: 10.1002/macp.1989.021900720
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic acid as a comonomer in radical polymerizations

Abstract: Cinnamic acid affects the initiation processes when methyl methacrylate is polymerized at 60 " C using benzoyl peroxide as initiator. Work with peroxide doubly-labelled with carbon-14 and tritium has shown that the balance between benzoate and phenyl end-groups is significantly shifted in favour of ester end-groups. On the other hand, study involving peroxide enriched with carbon-I 3 has given no evidence for the presence in the polymers of benzoate end-groups attached to units derived from cinnamic acid. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Therefore, here, we focus on crotonic acid and its derivatives as monomers. However, β-substituted α,β-unsaturated carboxylate monomers, such as alkyl crotonates and alkyl cinnamates, are not easily polymerized. , In fact, alkyl crotonates cannot be polymerized by the common radical initiators of azobisisobutyronitrile (AIBN) and rac -2,2′-azobis­(4-methoxy-2,4-dimethylvaleronitrile) (V-70L) (see Supporting Information). Moreover, in the past two decades, synthetic methods for poly­(alkyl crotonate)­s (PRCrs) have been infrequently studied. In one study, Ute et al showed that transition-metal Lewis acids, such as HgI 2 , catalyzed the GTP of various n -alkyl crotonates using 1-trimethylsiloxyl-1-methoxy-2-methyl-1-propene (MTS) as an initiator. In this study, we attempted the GTP of various alkyl crotonates with organic catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, here, we focus on crotonic acid and its derivatives as monomers. However, β-substituted α,β-unsaturated carboxylate monomers, such as alkyl crotonates and alkyl cinnamates, are not easily polymerized. , In fact, alkyl crotonates cannot be polymerized by the common radical initiators of azobisisobutyronitrile (AIBN) and rac -2,2′-azobis­(4-methoxy-2,4-dimethylvaleronitrile) (V-70L) (see Supporting Information). Moreover, in the past two decades, synthetic methods for poly­(alkyl crotonate)­s (PRCrs) have been infrequently studied. In one study, Ute et al showed that transition-metal Lewis acids, such as HgI 2 , catalyzed the GTP of various n -alkyl crotonates using 1-trimethylsiloxyl-1-methoxy-2-methyl-1-propene (MTS) as an initiator. In this study, we attempted the GTP of various alkyl crotonates with organic catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the difficulty of homopolymerizing cinnamates, several research groups have focused on their radical copolymerization with various comonomers, including MMA, [ 459,460 ] maleic anhydride, [ 461 ] fumarates, [ 462 ] methyl acrylate, [ 460 ] acrylonitrile, [ 460 ] or electron‐donating styrene. [ 460,463–468 ] M n of the order of 10 000 g mol −1 could be obtained but the incorporation of cinnamates was generally low. Recently, Kamigaito and co‐workers reported for the first time the use of reversible‐deactivation radical polymerization techniques such as ATRP, RAFT, and NMP for the copolymerization of 1:1 mixtures of cinnamates with styrene or methyl acrylate.…”
Section: Polymerization Of (Meth)acrylic Monomers and Analogsmentioning
confidence: 99%
“…However, cinnamic acid and its derivatives are difficult to homopolymerize and only give oligomers due to the steric hindrance around the vinyl group, similar to what is seen with most 1,2-disubsituted vinyl monomers . While radical copolymerizations between cinnamic monomers and other vinyl monomers such as styrene have been studied in conventional radical polymerizations, the copolymerizability of such monomers is generally low and only results in copolymers with low cinnamic monomer incorporations. As is obvious from its low copolymerizability, there have been almost no studies on the properties of the copolymers of cinnamic monomers or on their controlled/living radical copolymerizations. Although cinnamoyl groups have been extensively used as platforms for the modification or functionalization of synthetic polymers via specific photoinduced [2 + 2] dimerizations, vinyl groups are rarely used as polymerizable groups for preparing functional polymers.…”
Section: Introductionmentioning
confidence: 98%